Cellular Calcium Signals in Cancer Chemoprevention and Chemotherapy by Phytochemicals. (25th July 2022) - Li, Xue; Miao, Shuhan; Li, Feng; Ye, Fen; Yue, Guang; Lu, Rongzhu; Shen, Haijun; Ye, Yang
Abstract: Identifying novel agents for cancer treatment is critical because of obstacles with anticancer drug resistance and lack of drug effectiveness. Intracellular calcium ion (Ca 2+ ), a common second messenger, regulates various cellular pathophysiological processes including cell proliferation, differentiation and apoptosis. Recent studies have shown that the remodeling of Ca 2+ signals is associated with cancer occurrence, progression and metastasis. Ca 2+ channels, transporter and pumps regulate calcium movement, and alteration of Ca 2+ signal component expression/activity is associated with numerous cancer cell activities. Therefore, targeting Ca 2+ signals is an attractive research focus in cancer treatment. Phytochemicals, secondary metabolites in plants, exhibit multifaceted effective anticancer activities in various cancers. Although the mechanisms of the anticancer effects of phytochemicals remain unclarified, studies have indicated that many phytochemicals inhibit cancer progression through modulating calcium signals. In this review, we summarize the phytochemicals with demonstrated anticancer effects through their influence on calcium signaling, which may provide new ideas and directions in cancer research.